Inducing memristive behavior to MoSe2/graphene bilayer using plasma treatment - Salehi, Mohammad; Mohseni, Seyed Majid; Bastani, Parnia; Jamilpanah, Loghman; Shokri, Babak (Scientific reports, 2025)
Two-dimensional (2D) materials promise novel functional electronic device applications due to their unique electronic band structure. Their electronic properties can be manipulated externally to make them suitable for application in advanced electronic components such as memory effects. One solution for applying such materials in memory devices is found to be based on the presence of defects in the lattice of such 2D materials. Among the various techniques in defect engineering, plasma treatments stand out as a highly selective and efficient method for modifying 2D materials. Here, we present plasma treatments as a versatile method for inducing memory effects in 2D materials via structural modifications. We use oxygen plasma treatment on MoSe 2 layers where modifications induce memristive properties in the material. We use Raman spectroscopy to observe the induced oxygen defects by plasma treatment. The scanning electron microscopy images show that the geometrical modifications also occur in the MoSe 2 , and the hexagonal 2D flakes become exfoliated. We discuss the possible effect of induced oxygen in the structure and geometrical evolution to uncover the origin of the observed memristive behavior in the plasma-treated MoSe 2 layers. The resulting memristive behavior initiates promising endurance signatures, which makes our method attractive for actual device manufacturing.